Avaliação comparada do uso de linguagens de indexação em catálogos de bibliotecas universitárias para recuperação por assunto - Boccato, Vera Regina Casari [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP]; Gil Leiva, Isidoro (My University, 2011)
A comparative evaluation was made of the use of natural language versus two specialized indexing languages, aiming to demonstrate the influence of the availability of indexing languages on the functioning of information retrieval systems. The study was conducted within the ambit of the construction of search strategies by subject in online university library catalogs. The precision ratio was calculated to determine the accuracy of each indexing language in subjectbased information retrieval. From the comparative evaluation of the use of indexing languages, it was concluded that the term specificity required by the user during retrieval was more satisfactory when the query was made through controlled languages, whose availability and simplicity is also an indispensable requisite.
Comparative evaluation of the use of indexing language in catalogs of university libraries for subject retrieval
Keywords: Indexing languages; Online catalogs; Subject retrieval; University libraries